Uji Efektivitas Daya Hambat Ekstrak dan Perasan Lidah Buaya (Aloe barbadensis Miller) pada Bakteri Staphylococcus Aureus dengan Metode Difusi - Farah Adilah Ambar Sari; Suliati Suliati; Syamsul Arifin; Dwi Krihariyani (Pusat Riset dan Inovasi Nasional, 2024)
Aloe vera is a plant that is rich in minerals, vitamins, and antibacterial properties. A study to analyze the antibacterial effectiveness of aloe vera in inhibiting the growth of Staphylococcus aureus bacteria isolated from acne pus. This study was an experimental laboratory study using the disc diffusion method, located at the Bacteriology Laboratory, Department of Medical Laboratory Technology, Poltekkes Kemenkes Surabaya, from February to May 2024. There were 6 sample treatments with 4 replications, 4 treatments of extract and juice concentration variations, namely concentrations of 70%, 80%, 90%, 100%, positive control using penicillin antibiotics, and negative control using clean distilled water. The results of this study show that at aloe vera extract concentrations of 70%, 80%, 90%, and 100%, the average diameter of the inhibition zone was 9 mm, 10 mm, 11 mm, and 12 mm, respectively, while in aloe vera juice, these concentrations did not form an inhibition zone. So it was concluded that aloe vera extract is more effective than aloe vera juice, the most successful test material to slow the growth of Staphylococcus aureus bacteria in this study was aloe vera extract with a concentration of 100%. This study also conducted qualitative phytochemical testing on aloe vera extract which has antibacterial compounds, namely saponins, tannins, flavonoids, and terpenoids. The results of the study on the effectiveness of the inhibitory power of aloe vera extract and juice against Staphylococcus aureus bacteria using the disc diffusion method were analyzed using quantitative descriptive and presented in tabulation form in the form of the diameter of the inhibition zone formed.